ANALYSIS OF LOVE IN “THE BROKEN WINGS” BY KAHLIL GIBRAN - Tira Nur Fitria (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
Love is a priceless gift and without it, life feels empty. Therefore, keep love with loyalty, honesty, and be able to keep our heart from being stained just for self-satisfaction which will regret in the end. This expression may as the basis for the writing of the novel "Broken Wings" by Khalil Gibran, a poet, philosopher, and painter from Lebanon. This work is considered very beautiful and tells the story of the fate that broke the wings of Gibran's love for a Lebanese girl named Selma Karamy. The objective of this research is to describe the meaning of love found in “The Broken Wings” by Kahlil Gibran. Love is the main theme in this story. The love in it is not only for Gibran to Selma Karamy, but also Selma Karamy's affection for his father is a form of love. Selma Karamy, who is starting to grow up, feels restless about her father. He realized that she was a woman. "Indeed, the tears of an old man are more meaningful than the tears of youth”. Love is not only for lovers, a child can give love to his parents. But, in the novel Wings of Broken, the love of a couple is highlighted. With his extraordinary sensitivity, Kahlil Gibran weaves a love story about a beautiful and passionate couple. The strength of this novel lies in its poetic lyrics which are full of meaning and the criticism it conveys. Love is interpreted as an attempt to love, do not have to have a loved one. Because in the end all will be returned to God, the Owner of Love. In this case, Gibran sees Selma as a ray of light that leads him to understand the meaning of life. Selma led Gibran to enter willingly into the paradise of pure love and truth with her sweetness and love. In The Broken Wings, Gibran uses the story of Adam and Eve to illustrate his story. When the love has died (or forced to die), what remains is only a row of sorrow that resides on the tomb. Leaving sweet dreams and painful memories behind. Just like a broken wing, unable to flap anymore.